Local Governance in Hungary – the Balance of the Last 20 Years - Pálné Kovács, Ilona (Discussion Papers, 2012)
The objective of the present study is to give an overview of the development of the Hungarian local government system in light of international development trends. The author’s aim is to provide a comprehensive evaluation of the spatial frameworks of public power practice in an international and theoretical context with an emphasis on Hungarian specifics. The actual relevance of drawing up a balance is justified by the fact that the institutional framework of local governments was created 20 years ago at the change of regime, and so the time is ripe to evaluate the experiences of their operation, the more so since the reform of territorial public administration is proposed regularly. On the basis of examining the past twenty years, the author would like to take a stance about whether the Hungarian system of local government has been able to transform the previous centralised Hungarian state, and to what extent it may provide an ideal framework for the democratic functioning of local power and the organisation of local administration and services. Where do we stand today and where lies our destination? It is inevitable to reflect on to what extent the Hungarian system of territorial governance is compatible with the European administrative space. Concerning the realisation of the recommendations, the evaluations produced later on have remained quite cautious. On the one hand, it was declared that significant reform programmes had been implemented in several Eastern Central European countries, which nonetheless were halted in several cases. In the evaluation of the Hungarian system of public administration, the present study will examine the evolution of centralisation/decentralisation, as well as the agents of local governance and their relations; and all this in light of the prevailing European processes.